Comparison of mechanical properties and shaping performance of ProGlider and ProTaper ultimate slider - Jeyi Song; Ji-Hyun Jang; Seok Woo Chang; Shin Hye Chung; Soram Oh (BMC Oral Health)
Abstract Background This study aims to compare design, phase transformation behavior, and torsional resistance of the ProGlider (PG) and ProTaper ultimate slider (PUS) and to compare the performance of two files in the glide-path preparation of a double-curved artificial canal. Methods Scanning electron microscopy, micro-computed tomography, and differential scanning calorimetry were used to characterize the samples. A torsional resistance test was performed to obtain ultimate strength and distortion angle. Simulated glide-path preparation was conducted with a double-curved resin canal, and both PG and PUS were operated on by 300 and 400 rpms. Maximum screw-in force, torque generated during canal shaping, number of pecking strokes to reach the apex were compared between groups. After canal shaping centering ratio and alteration of files were assessed. Statistical analyses were performed using the Mann-Whitney U test, and the Kruskal-Wallis test with Bonferroni correction. A p value less than 0.05 was considered significant. Results While the PG had a square cross-section, the PUS had variable square and rhomboid cross-sections and alternating cutting-edge. PG and PUS have austenitic transformation starting and finishing temperatures of 24–25℃, and 57–59℃, respectively. Ultimate strength of PUS are superior to that of PG, whereas the distortion angle of PG is greater than that of PUS (p < 0.05). The maximum screw-in force and clockwise torque generated during glide-path preparation were highest in the PUS group rotated at 300 rpm (p < 0.05). Shaping with the PG at 300 rpm and shaping with the PUS at 400 rpm exhibited comparable maximum screw-in forces. There were no significant differences in the number of pecking strokes to reach the apex and centering ability among groups shaped with PG and PUS at both rotation speeds. PG shaped at 400 rpm demonstrated severe alteration on its surface, while PUS shaped at 300 and 400 rpms exhibited comparable surface alterations. Conclusions PG has a constant square cross-section, while PUS has a variable cross-section and alternating cutting-edge. Using PUS at recommended speed of 400 rpm ensures safe use with minimal screw-in force and surface alteration. At recommended speeds, both PG and PUS perform comparably and are safe for double-curved canals.